P144 Meet Mr Foul! An innovative approach to get to the heart of distress: A therapeutic tool to work with patients in 'externalising' illness, symptoms and their consequences. (1st October 2013) - McLaughlin, Kimberley
Abstract : Context: Introduced to the field of family therapy in the 1980s, 'externalising' practice aims to enable people to realise that they and the problem are not the same thing. Externalising the problem encourages a separation from the problem - 'the person is not the problem, the problem is the problem' (White 2007:9). A space is created between the person and whatever is troubling them. Often problems become 'internalised'; with patients seeing illness as something wrong with them, that they or something about them is problematic. In Practice: Externalising helps us to shift self-blame. A patient living with Parkinson's disease said 'I'm so pathetic, so incompetent and such a burden…'. Externalising questions helped to reshape the relationship with Parkinson's e.g. 'How long has Parkinson's been influencing you?', 'What does Parkinson's tell you about yourself?', 'When is Parkinson's not so strong?'. Questions enabled collaborative exploration of the effects and tactics of problems and helped to reduce their influence. This encouraged separation from the problem, the patient began to see her symptoms as external to themself. Contributing to this process was her renaming Parkinson's as 'Mr Foul Disease'. Self-blame decreased and 'Mr Foul' became more manageable and less powerful. A sense of relief was experienced as the patient realised she was not the problem and became more able to reconnect stories about herself as 'capable, insightful and determined'. Discussion: Externalising conversations can be flexible, creative and encourage patients to use their own problem-solving strategies, skills. They provide palliative practitioners with a tool, which positions them alongside their patients' problems, jointly exploring of new ways of relating to illness and symptoms rather than a position of expertise.